Human Immunodeficiency Virus Type 1 Protease Triggers a Myristoyl Switch That Modulates Membrane Binding of Pr55(gag) and p17MA - Hermida-Matsumoto, Luz (American Society for Microbiology, 1999)
The human immunodeficiency virus type 1 (HIV-1) Pr55(gag) gene product directs the assembly of virions at the inner surface of the cell plasma membrane. The specificity of plasma membrane binding by Pr55(gag) is conferred by a combination of an N-terminal myristoyl moiety and a basic residue-rich domain. Although the myristate plus basic domain is also present in the p17MA proteolytic product formed upon Pr55(gag) maturation, the ability of p17MA to bind to membranes is significantly reduced. It was previously reported that the reduced membrane binding of p17MA was due to sequestration of the myristate moiety by a myristoyl switch (W. Zhou and M. D. Resh, J. Virol. 70:8540–8548, 1996). Here we demonstrate directly that treatment of membrane-bound Pr55(gag) in situ with HIV-1 protease generates p17MA, which is then released from the membrane. Pr55(gag) was synthesized in reticulocyte lysates, bound to membranes, and incubated with purified HIV-1 protease. The p17MA product in the membrane-bound and soluble fractions was analyzed following proteolysis. Newly generated p17MA initially was membrane bound but then displayed a slow, time-dependent dissociation resulting in 65% solubilization. Residual p17MA could be extracted from the membranes with either high pH or high salt. Treatment of membranes from transfected COS-1 cells with protease revealed that Pr55(gag) was present within sealed membrane vesicles and that the release of p17MA occurred only when detergent and salt were added. We present a model proposing that the HIV-1 protease is the “trigger” for a myristoyl switch mechanism that modulates the membrane associations of Pr55(gag) and p17MA in virions and membranes.